# User:1is0?

Jump to navigation
Jump to search

## Proof: $1 = 0$

Let $x = 0$. Then,

- $\dfrac x x = \dfrac 0 x$

- $1 = 0 \paren ?$

## Proof: $\map f {-x} = \map f x \implies \map {f'} {-x} = -\map {f'} x$

- $\dfrac {\d {\map f {-x} } } {\rd x} = \dfrac {\d {\map f x} } {\d x}$
- $\map {f'} {-x} = -\map {f'} x$

$\blacksquare$

I think you might want to explain that a little better. The notation is confusing at best. It may help to introduce an auxiliary function $\map g x = \map f {-x}$. --Dfeuer (talk) 18:19, 4 May 2013 (UTC)